Continuous personalized cerebrovascular reactivity-based physiologic metrics in neurocritical care: a narrative review of the current landscape, limitations, and future directions - Stein, Kevin Y.; Froese, Logan; Hasan, Rakibul; Sainbhi, Amanjyot Singh; Vakitbilir, Nuray; Bergmann, Tobias; Islam, Abrar; Silvaggio, Noah; Hayat, Mansoor; Zeiler, Frederick A. (Frontiers in Physiology, 2025)
Over the past several decades, significant progress has been made in our ability to achieve guideline-based cerebral physiologic targets for the management of moderate-to-severe traumatic brain injury (TBI). However, despite these advancements, there has been limited improvement in the long-term outcomes associated with this condition. It has been suggested that this is in part due to the generalized approach of current Brain Trauma Foundation guidelines. It has been demonstrated that significant heterogeneity in cerebral physiologic response to TBI exists between patients, and that it involves highly dynamic physiologic mechanisms which vary across a patient’s time in the ICU. Therefore, an individualized management approach, that accounts for individual phenotype, injury heterogeneity, and the dynamic nature of cerebral physiology, is urgently needed. Recently, multiple personalized physiologic metrics, based on cerebrovascular reactivity optimization, have been proposed as potential tools to help address this increasingly important issue. These include the cerebral perfusion pressure optimum (CPPopt), mean arterial pressure optimum (MAPopt), bispectral index optimum (BISopt), and individualized intracranial pressure (iICP) thresholds. These metrics aim to shift neurocritical care management from static, population-based targets to dynamic, personalized targets that are tailored to a patient’s real-time cerebral physiologic needs. In this narrative review, we will cover the topic of continuously derived cerebrovascular reactivity-based personalized physiologic metrics in neurocritical care, including the current states of the various existing techniques, their limitations, and future directions.